Analysis of The Association Between Nutrient Intake and Bone Mineral Density in College Students - Dian Isti Angraini; Firdawati Firdawati; Yaktiworo Indriani (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: Osteoporosis is a condition characterized by brittle bone prone to fracture. The risk increases significantly with age, particularly among women. An effective approach for understanding and preventing the progression of osteoporosis is by examining bone mineral density (BMD), with diet playing an essential role. Therefore, this study aimed to analyze the association between nutrient intake and BMD in female students at the University of Lampung.Method: This analytical observational study adopted a cross-sectional design. A total of 150 female students at the University of Lampung, were selected as samples using a multistage random sampling technique. The study variables were BMD and nutrient intake, specifically calcium, phosphorus, magnesium, vitamin C, vitamin D, and protein. BMD was assessed based on examination using an ultrasound bone densitometer, while nutrient intake was measured through 2x24h food recall. In the process, data analysis was conducted using the chi-square test.Result: The results showed that female students had BMD in the osteopenia category of 52.7% and osteoporosis of 10%. Calcium and phosphorus intake were associated with BMD in Lampung University female students (p<0.01; p=0.11), while intake of magnesium, vitamin C, vitamin D, and protein did not correlate (p=0.751; p=0.382; p =0.41; p=0.694). Therefore, meeting calcium and phosphorus needs from an early age is essential to prevent osteoporosis.